KEDUDUKAN HUKUM UANG ELEKTRONIK (E-MONEY) FLAZZ DALAM TRANSAKSI PEMBAYARAN NON-TUNAI: TINJAUAN DARI PERSPEKTIF HUKUM PERBANKAN DI INDONESIA - Diana Natalia Sari; Sherly Nelsa Fitri (PSHPM Untag Semarang, 2025)
This study discusses the legal status of electronic money (e-money) Flazz in non-cash transactions in Indonesia from a banking law perspective. The research method applied is normative with a statutory approach and doctrinal analysis of related regulations, including Bank Indonesia Regulation No. 20/06/PBI/2018 concerning Electronic Money and Bank Indonesia Law No. 6 of 2009. The findings of this study show that Flazz as electronic money is legally recognized in the payment system in Indonesia, equivalent to other non-cash payment instruments such as debit cards and QRIS. Although Banking Law No. 10 of 1998 does not specifically regulate e-money, the new regulation from Bank Indonesia has provided a clear legal basis. Flazz provides benefits in daily transactions, although there are limitations in transaction value and its use abroad. Regulations also ensure security and protection for Flazz users.